MANAGING THE DEVELOPMENT OF SOCIO-ECONOMIC SYSTEMS - Nurmamatova Sevara Kamol qizi,; Ruzmetova Diana Komilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT The advancement of socio-economic systems demands thorough management strategies that incorporate economic, social, technological, and institutional elements. This  article  explores  the  characteristics  of  socio-economic  systems,  the  principles guiding  their  management,  and  modern  methods  that  promote  sustainable development.  It  also  highlights  significant  challenges  and  provides  suggestions  for improving management processes in today's world.